2020
DOI: 10.1101/2020.08.11.245894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-evolutionary signals fromBurkholderia pseudomalleigenomics identify its survival strategies and highlight improving environmental health as prevention policy

Abstract: The soil bacterium Burkholderia pseudomallei is the causative agent of melioidosis and a significant cause of human morbidity and mortality in many tropical and sub-tropical countries. The species notoriously survives harsh environmental conditions but the genetic architecture for these adaptations remains unclear. Here we employed a powerful combination of genome-wide epistasis and co-selection studies, gene expression analysis, and gene knockout assays to uncover genetic markers that have been repeatedly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 90 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…An experimental study further reported that a gene of inner core LPS biosynthesis cluster ( waaE: BPSL2510) is vital for a long-term water incubation ( Moore et al, 2008 ). Moreover, an adhesin BPSL1661 was identified as a hub for co-evolutionary signals in B. pseudomallei population ( Chewapreecha et al, 2020 ). The gene was functionally characterized as essential during nutrient starvation ( Chewapreecha et al, 2020 ), thereby highlighting nutrient limitation as a major evolutionary pressure experienced by this microorganism.…”
Section: Natural Selection In Genes Required For Host-pathogen Interamentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental study further reported that a gene of inner core LPS biosynthesis cluster ( waaE: BPSL2510) is vital for a long-term water incubation ( Moore et al, 2008 ). Moreover, an adhesin BPSL1661 was identified as a hub for co-evolutionary signals in B. pseudomallei population ( Chewapreecha et al, 2020 ). The gene was functionally characterized as essential during nutrient starvation ( Chewapreecha et al, 2020 ), thereby highlighting nutrient limitation as a major evolutionary pressure experienced by this microorganism.…”
Section: Natural Selection In Genes Required For Host-pathogen Interamentioning
confidence: 99%
“…Moreover, an adhesin BPSL1661 was identified as a hub for co-evolutionary signals in B. pseudomallei population ( Chewapreecha et al, 2020 ). The gene was functionally characterized as essential during nutrient starvation ( Chewapreecha et al, 2020 ), thereby highlighting nutrient limitation as a major evolutionary pressure experienced by this microorganism. The presence of B. pseudomallei is strongly associated with the low-nutrient soil ( Limmathurotsakul et al, 2010b ; Hantrakun et al, 2016 ).…”
Section: Natural Selection In Genes Required For Host-pathogen Interamentioning
confidence: 99%
See 1 more Smart Citation